Pembentukan Sekolah Orang Tua Hebat sebagai Upaya Mendukung Kebijakan Pengembangan Anak Usia Dini Holistik Integratif - Larasati, Dewi Citra; Dekki Umamur Ra’is; Abd Rohman (Forum Kerjasama Pendidikan Tinggi, 2023)
The importance of the role of the family is a priority for the Government of Indonesia, resulting in the issuance of the Holistic Integrative Early Childhood Development Policy (PAUD HI). PAUD HI is an effort made to fulfil the diverse and interrelated essential needs of children in a simultaneous, systematic and integrated manner (from the aspects of health, education and care). One of the intensification efforts in the field of parenting is known as The Great Parents (SOTH). Pandanwangi Village has not yet established SOTH, even though Pandanwangi Village is one of the 10 villages that are the locus of stunting. Therefore, assistance is needed so that SOTH can be formed by providing assistance such as: contacting relevant stakeholders, forming SOTH administrators, reviewing the curriculum, and conducting socialisation to prospective SOTH participants.